MENGULAS FAKTOR PENDUKUNG DAN PENGHAMBAT KEBERHASILAN PENGUATAN KARAKTER PROFIL PELAJAR PANCASILA DI SEKOLAH 3T - Mahdiansyah; Sukirno; Wahyudi (Jurnal Genta Mulia, 2024)
Strengthening the profile of Pancasila students is realized in a character strengthening program that has been implemented in several schools in the Frontier, Outermost and Disadvantaged (3T) areas. This article aims to review the supporting factors for the success of strengthening the character of Pancasila students, and the factors inhibiting the strengthening of the character of Pancasila students in 3T schools. The research method used is qualitative which is presented descriptively. Data collection techniques are carried out through interviews, observation and documentation. The research location took various levels of schools in the 3T area category in Sungai Tubu District, Malinau Regency, North Kalimantan Province. The research results obtained are that the Pancasila student profile aims to shape the character of students according to Pancasila values. Supporting factors for the success of strengthening the character profile of Pancasila students in 3T schools include the vision and mission of rural schools which prioritize character education, the seriousness of teachers in educating and the independence of the students themselves. Meanwhile, inhibiting factors include limited school facilities, difficult accessibility to school locations, low literacy, differences in student characteristics and the negative influence of smartphone use.